2015
DOI: 10.1002/pssr.201510214
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cr-doped Sb2 Te3 films and their application to phase-change memory

Abstract: Phase‐change memory (PCM) is regarded as one of the most promising candidates for the next‐generation nonvolatile memory. Its storage medium, phase‐change material, has attracted continuous exploration. Along the traditional GeTe–Sb2Te3 tie line, the binary compound Sb2Te3 is a high‐speed phase‐change material matrix. However, the low crystallization temperature prevents its practical application in PCM. Here, Cr is doped into Sb2Te3, called Cr–Sb2Te3 (CST), to improve the thermal stability. We find that, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…A small shift to 530.5 eV in the present case for the sample with the lowest doping concentration ( x = 0.15) can be attributed to surface oxidation (labelled with arrows). Upon increasing the Cr concentration, the peaks shift towards the un-oxidized, pristine value of 528 eV, thus indicating that the doping with Cr prevents further oxidation of Sb 2 Te 3 , consistent with earlier reports 11 , 22 . In other words, Cr atoms are more prone to oxidation compared to the Sb atoms, and upon substitution, the degree of surface oxidation of the sample is reduced.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…A small shift to 530.5 eV in the present case for the sample with the lowest doping concentration ( x = 0.15) can be attributed to surface oxidation (labelled with arrows). Upon increasing the Cr concentration, the peaks shift towards the un-oxidized, pristine value of 528 eV, thus indicating that the doping with Cr prevents further oxidation of Sb 2 Te 3 , consistent with earlier reports 11 , 22 . In other words, Cr atoms are more prone to oxidation compared to the Sb atoms, and upon substitution, the degree of surface oxidation of the sample is reduced.…”
Section: Resultssupporting
confidence: 91%
“…This has led to the recent experimental observations of the topological magnetoelectric effect 7 , induction of a magnetic monopole 8 and the quantum anomalous Hall effect (QAHE) 9 . Hence a wide range of potential industrial applications have found their way into the literature such as magnetic sensing 10 , information storage 10 , phase change memories 11 and various spin injectors for spintronic devices 12 . In the quantized version of the anomalous Hall effect (AHE), the topologically protected state has a dissipationless current flowing along the edge of a 2D surface of a magnetically doped TI in the absence of a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in very good accordance with previous crystallographic studies of the Sb 2 Te 3 material. 21,[24][25][26] The difference of the peak amplitudes is attributed to the different annealing surfaces. In the case of oven annealing the whole sample surface was annealed, while in the case of laser annealing a surface area of approximately 1 cm 2 was crystallized.…”
mentioning
confidence: 99%
“…This has led to the recent experimental observations of the topological magnetoelectric effect 8 , induction of a magnetic monopole 9 and the quantum anomalous Hall effect (QAHE) 10 . Hence a wide range of potential industrial applications have been demonstrated in literature such as magnetic sensing 11 , information storage 11 , phase change memories 12 and various spin injectors for spintronic devices 13 . In the quantized version of the anomalous Hall effect (AHE), the topologically protected state has a dissipationless current flowing along the edge of a 2D surface of a magnetically doped TI in the absence of a magnetic field.…”
Section: Introductionmentioning
confidence: 99%